High-energy approximations to nuclear scattering - Schürmann, Bernd (Department of Physics, 2016)
We study high-energy approximations to nuclear scattering. These are based on expansions of the free-particle propagator. We distinguish the eikonal expansion and the Fresnel expansion and interpret their physical meaning in optical terms. A "Fresnel approximation" is defined as a partial sum of the eikonal expansion which describes Fresnel diffraction effects. In Fresnel approximation we derive, by means of a unitary transformation, a closed representation of the scattering amplitude which is formally similar to the corresponding expression irt Glauber's high-energy scattering theory. The corrections to the Glauber model of first order in the reciprocal wave number are given by the second-order eikbnal approximation. These are evaluated explicitly for high energy elastic scattering of protons from light nuclei (⁴He, ¹²C, ¹⁶O).